Web of Spider-Man - Shinick, Kevin, 1969- (Marvel Worldwide, Inc., 2021)
Spider-Man joins a group of teenage scientists at Tony Stark's research station, the Worldwide Engineering Brigade (WEB), hoping to use the technology to fight crime around the world, but the group quickly comes under attack from a hologram virus manifesting itself as the Green Goblin.